Returns in commodities futures markets and financial speculation: A multivariate GARCH approach - Matteo Manera; Marcella Nicolini; Ilaria Vignati (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper analyses futures prices for four energy commodities (light sweet crude oil, heating oil, gasoline and natural gas) and five agricultural commodities (corn, oats, soybean oil, soybeans and wheat), over the period 1986-2010. Using CCC and DCC multivariate GARCH models, we find that financial speculation is poorly significant in modelling returns in commodities futures while macroeconomic factors help explaining returns in commodities futures. Moreover, spillovers between commodities are present and the conditional correlations among commodities are high and time-varying.
Keywords: C32; G13; Q11; Q43; 330; Energy; Commodities; Futures Markets; Financial Speculation; Multivariate GARCH